International Technical Digest on Electron Devices Meeting 1992
DOI: 10.1109/iedm.1992.307438
|View full text |Cite
|
Sign up to set email alerts
|

The effects of furnace N/sub 2/O annealing on MOSFETs

Abstract: Abstruc#-MOSFETswith 70-110A thick furnace N20-annealed gate oxides are examined at both room and liquid nitrogen temperatures. The N 2 0 anneal not only improves device performance, e.g. by increasing the high normal field mobility and current drivability, but it also suppresses degradation induced by Fowler-Nordheim and channel hot-carrier injection. Random telegraph noise measurements reveal a possible correlation between the interface properties and the mobility. OPM 95lPcmW m J W

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…It has been shown that nitridation of the gate oxide can provide a barrier to boron penetration [16], [17]. Nitrided gate oxides also have exhibited improved hot-carrier reliability, and reduced radiation degradation [16], [18]. Nitridation of the gate oxide has been shown to affect surface carrier mobility, but its effect on saturation velocity has not been studied.…”
Section: A Nitridation Of the Gate Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that nitridation of the gate oxide can provide a barrier to boron penetration [16], [17]. Nitrided gate oxides also have exhibited improved hot-carrier reliability, and reduced radiation degradation [16], [18]. Nitridation of the gate oxide has been shown to affect surface carrier mobility, but its effect on saturation velocity has not been studied.…”
Section: A Nitridation Of the Gate Oxidementioning
confidence: 99%
“…Namely, at low effective vertical fields a nitrided sample has electron mobility less than the "universal" value, while at high vertical fields the trend is reversed. The crossover point has been shown to be a function of N O anneal time and temperature [18]. Normally, shorter times and lower temperatures lead to crossovers at lower vertical fields.…”
Section: A Linear Mobility At Low Tangential Fieldmentioning
confidence: 99%
“…is the highest for thermal oxide and is degraded for the N Oannealed oxides. It is apparent that this reduction in is dominated by degradation of peak electron mobility in N-MOSFET's [1], [3].…”
Section: A Initial Propertiesmentioning
confidence: 96%
“…Okada et al showed that although the N O-nitridation significantly improved time-dependentdielectric-breakdown (TDDB) characteristics under substrateside injection, it did not improve the TDDB characteristics under gate-side injection [4]. The N O-nitrided oxides were also known to exhibit inferior MOSFET characteristics due to Si/SiO interface charges [5]- [7]. In fact, these disadvantages have hindered the popular use of N O-nitrided oxides for the commercial production.…”
Section: Introductionmentioning
confidence: 99%